Empowering Arabic Language Educators in the Digital Age: A Participatory Action Research on Integrating AI-Driven Pedagogy in Rural Schools - Putri Julia Ningsi; Ahmed Al Fahad; Mona Al Johani; Ana Durrotul Hikmah (Pengabdian: Jurnal Abdimas, 2026)
Background. The digital age has introduced Artificial Intelligence (AI) to transform education. However, rural schools often lack these opportunities. This research investigates how AI-driven pedagogy can empower Arabic language teachers in underserved rural communities. Purpose. The study's primary objective is to evaluate the impact of AI tools on teaching practices. Specifically, it assesses how AI can enhance pedagogical effectiveness, increase student engagement, and ultimately improve learning outcomes in Arabic language classes. Method. The research utilized a Participatory Action Research (PAR) approach. Teachers actively participated in the research process, experimenting with AI tools, reflecting on their use, and adapting their teaching strategies. Data were collected via interviews, observations, and feedback surveys. Results. Findings demonstrate significant improvements. AI tools enhanced instructional effectiveness and facilitated personalized learning. This led to increased student interest and participation in Arabic lessons. Teachers also reported greater satisfaction in meeting diverse student needs. Conclusion. AI is crucial for empowering rural educators. By providing tools for personalized and effective instruction, AI integration helps bridge educational gaps. This fosters a more inclusive and sustainable learning environment in underserved rural settings.